2016
DOI: 10.1177/1066896916672556
|View full text |Cite
|
Sign up to set email alerts
|

Composite Blastoid Variant of Mantle Cell Lymphoma and Classical Hodgkin Lymphoma

Abstract: Composite lymphoma (CL) describes the rare occurrence of 2 or more distinct types of lymphoma in a single anatomical location. We present the case of a 78-year-old man presenting with a 3-month history of weakness, malaise, and increasing dyspnea. A lymph node excised from the posterior triangle of the neck revealed the coexistence of 2 morphologically and phenotypically distinct lymphoid neoplasms consistent with a blastoid variant of mantle cell lymphoma (MCL) occurring in composite with classical Hodgkin ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The clinical significance of HRS-like cells in MCL remains to be clarified. The reported cases were rarely managed with CHL appropriate regimens (Caleo et al 2003; Tinguely et al 2003; Hayes et al 2006; Schneider et al 2014; Giua et al 2015; Murray et al 2017; Kramer et al 2019), which is consistent with the current recommendations for management of CLL/SLL with “type I” HRS-like (Swerdlow et al 2017). Once a diagnosis of bona fide CHL is established, management with CHL appropriate regimen would be reasonable as demonstrated by control of CHL component in this case.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The clinical significance of HRS-like cells in MCL remains to be clarified. The reported cases were rarely managed with CHL appropriate regimens (Caleo et al 2003; Tinguely et al 2003; Hayes et al 2006; Schneider et al 2014; Giua et al 2015; Murray et al 2017; Kramer et al 2019), which is consistent with the current recommendations for management of CLL/SLL with “type I” HRS-like (Swerdlow et al 2017). Once a diagnosis of bona fide CHL is established, management with CHL appropriate regimen would be reasonable as demonstrated by control of CHL component in this case.…”
Section: Discussionsupporting
confidence: 81%
“…Clonally related HRS-like cells in MCL have only been reported in three prior cases (Supplemental Table S4; Schneider et al 2014; Murray et al 2017; Kramer et al 2019). In these studies, the clonal relationship was established by PCR studies of the IGHV regions after microdissection (Schneider et al 2014; Murray et al 2017) and confirmed by FISH studies showing IGH/ CCND1 translocation in both MCL and HRS-like cells (Schneider et al 2014; Murray et al 2017; Kramer et al 2019). Our case is exceptional as a bona fide CHL was diagnosed rather than MCL with HRS c-like cells, and a MCL component was not present in the biopsy with CHL either by flow cytometric study (with a sensitivity approaching 0.01%) or immunohistochemical studies (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the co‐existence of MCL and cHL is rare, and only eight cases have been described 5–11 . Of these, HRS cells were clonally related to the coexisting MCL in four cases 6,9–11 and unrelated in the remaining two 7 . A case of MCL, which relapsed with the presence of HRS‐like cells 9 years after autologous peripheral blood stem cell transplantation (auto‐PBSCT) is presented.…”
Section: Iintroductionmentioning
confidence: 99%